2009
DOI: 10.1029/2009jd011900
|View full text |Cite
|
Sign up to set email alerts
|

Probing into regional O3 and particulate matter pollution in the United States: 2. An examination of formation mechanisms through a process analysis technique and sensitivity study

Abstract: Following a comprehensive model evaluation in part 1, this part 2 paper describes results from 1 year process analysis and a number of sensitivity simulations using the Community Multiscale Air Quality (CMAQ) modeling system aimed to understand the formation mechanisms of O3 and PM2.5, their impacts on global environment, and implications for pollution control policies. Process analyses show that the most influential processes for O3 in the planetary boundary layer (PBL) are vertical and horizontal transport, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 60 publications
(99 reference statements)
6
111
0
Order By: Relevance
“…Consequently, there were peak PM 2.5 mass concentration at the nighttime of 13 and 14 December until the diffusion process provided an important pathway for the PM 2.5 removal in the morning of 14 and 15 December under the influence of wind speed increase. By design, the gas-phase chemistry process is accounted as part of aerosol process rather than as a direct contribution to PM 2.5 formation (Zhang et al, 2009b). The pollutants transported from the north of Zhejiang province and Jiangsu province made important contributions to the PM 2.5 production at the industrial station during the episode.…”
Section: Process Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there were peak PM 2.5 mass concentration at the nighttime of 13 and 14 December until the diffusion process provided an important pathway for the PM 2.5 removal in the morning of 14 and 15 December under the influence of wind speed increase. By design, the gas-phase chemistry process is accounted as part of aerosol process rather than as a direct contribution to PM 2.5 formation (Zhang et al, 2009b). The pollutants transported from the north of Zhejiang province and Jiangsu province made important contributions to the PM 2.5 production at the industrial station during the episode.…”
Section: Process Analysismentioning
confidence: 99%
“…This technique does not require additional input variables. From CMAQ process analysis result, the relative importance of major atmospheric processes such as emissions of primary species, advection (including horizontal and vertical advection, and advection adjustment), diffusion (including horizontal and vertical diffusion), dry deposition, gas-phase chemistry (including photolysis and kinetic reactions), could process, aerosol process (Zhang et al, 2009b) are examined. Cloud process includes the net effect of cloud attenuation of photolysis rates, convective and nonconvective mixing and scavenging by clouds, aqueousphase chemistry, and wet deposition.…”
Section: Process Analysismentioning
confidence: 99%
“…Jonson et al, 2006;van Loon et al, 2007;Vautard et al, 2007;Gilliland et al, 2008;Zhang et al, 2009bZhang et al, , 2013Colette et al, 2011;Godowitch et al, 2011;Hogrefe et al, 2011;Zubler et al, 2011). It has been demonstrated that uncertain emission inventories, data assimilation approaches used in meteorology models, and initial/boundary conditions can influence dynamic evaluation of model-predicted changes in ambient air quality (Napolenock et al, 2011;Kang et al, 2012).…”
Section: A Baklanov Et Al: Online Coupled Regional Meteorology Chemmentioning
confidence: 99%
“…Tropospheric column observations can be used to evaluate model performance in terms of relevant column output, examining emissions in a region, and drawing inferences for photochemical relationships among precursor species. They have been used to evaluate regional model results [Zhang et al, 2009;Muntaseer Billah Ibn Azkar et al, 2012;Kemball-Cook et al, 2015], in support of O 3 source assessment [McDonald-Buller et al, 2011], and for biogenic contribution assessment [Carlton and Baker, 2011]. The availability and use of satellite retrievals of air pollutant for model evaluation is incredibly useful to assess model performance in between surface monitors, important for ruralregional conclusions.…”
Section: Satellite Observations Supporting Model Results Evaluationmentioning
confidence: 99%
“…Limitations of satellite observations include temporal availability (i.e. once per day), and the fact that cloud or intense smoke coverage can obscure satellite imagery [Zhang et al, 2009;Muntaseer Billah Ibn Azkar et al, 2012]. Despite temporal and retrieval limitations, satellite observations provide a significant amount of data to evaluate a wide range of air quality phenomenon and circumstances.…”
Section: Satellite Observations For Air Quality Analysismentioning
confidence: 99%